2006
DOI: 10.1007/s11145-006-9005-2
|View full text |Cite
|
Sign up to set email alerts
|

Early literacy interventions: The relative roles of storybook reading, alphabetic activities, and their combination

Abstract: The study examined the differential contributions on vocabulary and alphabetic skills of three literacy programs: (a) storybook reading program; (b) alphabetic skills program; and (c) a combined program. It was expected that storybook reading would enhance primarily vocabulary while alphabetic skills training would promote primarily alphabetic skills. Program by age interactions were examined in two age groups (3-4 and 4-5 years old) to test whether the storybook reading program may be more productive for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 56 publications
7
66
0
Order By: Relevance
“…As in previous studies with hearing children (Aram, 2006;Aram & Biron, 2004), the current results indicate that the intervention was fruitful in enhancing the basic skills immanent to the acquisition of reading and writing of children with HL. Children who participated in the program progressed on these skills more than their peers who did not participate in the program.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…As in previous studies with hearing children (Aram, 2006;Aram & Biron, 2004), the current results indicate that the intervention was fruitful in enhancing the basic skills immanent to the acquisition of reading and writing of children with HL. Children who participated in the program progressed on these skills more than their peers who did not participate in the program.…”
Section: Discussionsupporting
confidence: 84%
“…Results indicated that the preschoolers who participated in the writing program significantly outperformed both the partici-pants in the storybook reading group and a control group on letter knowledge, phonological awareness, word writing, and orthographic awareness. In a second study, Aram (2006) examined the differential contributions of three preplanned, systematic intervention programs implemented by the preschool teacher -storybook, writing, and combined (storybook and writing) -on the language and alphabetic skills of preschoolers. In each program, the teacher worked with small groups of children twice a week for about 30 minutes.…”
Section: Early Literacy Interventions For Children With Hlmentioning
confidence: 99%
See 2 more Smart Citations
“…Reading the same book repeatedly to young children was found to support their oral language abilities and their emergent literacy knowledge (e.g., CAP, orthographic knowledge; Aram, 2006;Aram & Biron, 2004;Sénéchal, 1997;Whitehurst, et al, 1999). However, similarly to results on reading e-books individually, evidence for emergent literacy is inconsistent and limited (Stahl, 2003).…”
Section: Adult Instructionmentioning
confidence: 97%